2007
DOI: 10.1002/jcb.21536
|View full text |Cite
|
Sign up to set email alerts
|

Prostate inflammation and its potential impact on prostate cancer: A current review

Abstract: Recent studies have identified a role for inflammation in the development and progression of several cancers, such as liver, stomach and the large intestine. Data from several studies has shown correlations between soluble inflammatory mediators, such as cytokines, chemokines and growth factors. However, a direct relationship between inflammation and prostate cancer has yet to be identified. Two major hurdles currently exist which limit the study of this relationship are first that animal models available for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 52 publications
1
58
0
2
Order By: Relevance
“…Positive associations between CRP levels and risk of all-cancer and lung cancer have been consistently reported by several large epidemiological studies including a retrospective cohort study by Proctor et al (2010)with 223,303 noncancer patients and 22,715 cancer cases, a cross-sectional study by Lee et al (2011) with 80,781 participants and two nested case-control studies (Trichopoulos et al, 2006;Chaturvedi et al, 2010). In accordance with the result of previous meta-analysis (Heikkila et al, 2009), less epidemiologic studies suggested a significant association between the elevated CRP levels and an increased risk of prostate and breast cancer (Platz et al, 2004;Trichopoulos et al, 2006), although a role for chronic inflammation in prostate (Haverkamp et al, 2008) and breast cancer (Ben-Baruch, 2003) has been identified. More controversy seemed to be from colorectal cancer (Otani et al, 2006;Gur et al, 2011;Lee et al, 2011) and previous metaanalysis gave an inconsistent result (Tsilidis et al, 2008;Heikkila et al, 2009).…”
Section: Discussionsupporting
confidence: 67%
“…Positive associations between CRP levels and risk of all-cancer and lung cancer have been consistently reported by several large epidemiological studies including a retrospective cohort study by Proctor et al (2010)with 223,303 noncancer patients and 22,715 cancer cases, a cross-sectional study by Lee et al (2011) with 80,781 participants and two nested case-control studies (Trichopoulos et al, 2006;Chaturvedi et al, 2010). In accordance with the result of previous meta-analysis (Heikkila et al, 2009), less epidemiologic studies suggested a significant association between the elevated CRP levels and an increased risk of prostate and breast cancer (Platz et al, 2004;Trichopoulos et al, 2006), although a role for chronic inflammation in prostate (Haverkamp et al, 2008) and breast cancer (Ben-Baruch, 2003) has been identified. More controversy seemed to be from colorectal cancer (Otani et al, 2006;Gur et al, 2011;Lee et al, 2011) and previous metaanalysis gave an inconsistent result (Tsilidis et al, 2008;Heikkila et al, 2009).…”
Section: Discussionsupporting
confidence: 67%
“…Because prostatitis can also lead to spuriously elevated PSA levels in affected individuals, diagnosing CPPS could potentially improve the clinical utility of this blood test, which is used to diagnose prostate cancer. Finally, because CPPS may also promote the development of prostate cancer (39), the diagnosis and treatment of CPPS could possibly affect the incidence of this common malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that the frequency of cancer would be higher in people with recurrent prostate damage, as this would increase the prevalence of stem cells and the chance for mutagenesis in one of the stem cells. In fact, it has been well documented that men with chronic prostate inflammation, which causes damage that requires prostate lobe regeneration (and the increased presence of stem cells), are at a greater risk for prostate cancer (Haverkamp et al 2008, Klein & Silverman 2008, Bardia et al 2009). Interestingly, we have observed that chronic exposure to low testosterone also leads to prostate damage and the expansion of several putative prostate stem cell populations, including LinK/ Cd133C/Cd117C cells and LinK/Cd49f…”
Section: Ar In Prostate Cancer Initiationmentioning
confidence: 99%